Characteristics of solution to singular fractional differential equation with two Riemann-Stieltjes integral boundary value conditions - Zhang, Nan; Zhang, Lingling; Liu, Hongwei; Liu, Tao; Wang, Hui; Tian, Huimin (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The purpose of this paper is to study unique solution and iterative sequence of approximate solution for uniformly approaching unique solution to a new class of singular fractional differential equations with two kinds of Riemann-Stieltjes integral boundary value conditions by using some fixed point theorems. Because of different properties of the nonlinear terms and complexity of the boundary conditions in equations, we first probe several fixed point theorems of sum-type operators which expand many existing works in this research area. It is essential to point out that some conditions in our works greatly simplify the proof process of fixed point theorems. By applying the operator conclusions obtained in this paper, some sufficient conditions that guarantee the existence and uniqueness of solutions to singular differential equations are obtained, two iterative schemes that uniformly converge to the unique solution are given which provide computational methods of approximating solutions. As applications, some examples are provided to illustrate our main results.